Pembuatan Sushi dan Sate Buah Sebagai Alternatif Makanan Untuk Balita - Nining Tunggal Sri Sunarti; Winarsih Winarsih (Lembaga Pengembangan Kinerja Dosen, 2023)
One of the principles that must be considered in a balanced diet is food diversity. Children often refuse foods they don't like and only choose foods they like, so they need to be introduced to a variety of foods to optimize the achievement of balanced nutrition. Consumption of a variety of foods in toddlers can guarantee the completeness of the nutrients their bodies need, because each food contains a different source of nutrients, both in type and amount. Sushi is a popular food and easy to make. Sushi and fruit satay have good nutritional content for toddlers. Making sushi and fruit satay aims to provide food choices for toddlers that are nutritious and easy to make. The implementation of the activity was carried out by means of direct demonstrations, participants tried directly to make sushi and fruit satay with the ingredients provided. Participants were very enthusiastic doing the practice of making sushi and fruit satay.